2019
DOI: 10.3390/app9020267
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Triggering of Highly Undercooled Xylitol Using an Air Lift Reactor for Seasonal Thermal Energy Storage

Abstract: Bio-based glass-forming materials are now considered for thermal energy storage in building applications. Among them, Xylitol appears as a biosourced seasonal thermal energy storage material with high potential. It has a high energy density and a high and stable undercooling, thus allowing storing solar energy at ambient temperature and reducing thermal losses and the risk of spontaneous nucleation (i.e., the risk of losing the stored energy). Generally when the energy is needed, the discharge triggering of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…This storage concept has been demonstrated for a solar heating system [12,13] and showed potential for compact thermal energy storage systems in buildings [14]. Recently, Duquesne et al reported Xylitol [15] and Puupponen et al reported micro-structured polyol-polystyrene composites [16] as further promising materials with stable supercooling properties. To investigate the stability of PCM with stable supercooling (type B tests), dedicated test procedures are required.…”
Section: Introductionmentioning
confidence: 99%
“…This storage concept has been demonstrated for a solar heating system [12,13] and showed potential for compact thermal energy storage systems in buildings [14]. Recently, Duquesne et al reported Xylitol [15] and Puupponen et al reported micro-structured polyol-polystyrene composites [16] as further promising materials with stable supercooling properties. To investigate the stability of PCM with stable supercooling (type B tests), dedicated test procedures are required.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization occurred at the surface of the small drops generated at the liquid surface, when the primitive bubbles exploded into daughter bubbles. Duquesne et al [9] observed that mechanical agitation of a 400 ml xylitol sample contained in a glass beaker started to nucleate in only 5 s of mixing throughout the agitated region with an undercooling of 45ºC.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when crystallization takes place, it usually happens at low rates, which limits the discharging power obtained. To overcome such issues, different methods to crystallize polyols from their melt have been studied during the last years: seeding, mechanical stirring, local cooling, additives, and ultrasound-assisted crystallization [ 6 , 7 ]. However, those that have only local effects make them inefficient to counterbalance the slow crystal growth of many polyols.…”
Section: Introductionmentioning
confidence: 99%